Corpus-based critical discourse analysis of China's image in news discourse on carbon peak and carbon neutrality in China Daily - Zhuoran Li; Ronghui Zhao (Acta Psychologica)
Based on the corpus of news reports on carbon peak and carbon neutrality in China Daily, this study examines the national image constructed in news reports of the mainstream newspaper on China's “dual carbon” goals by investigating the use of the high-frequency lexical words, the co-occurrence network of words and collocation features from the perspectives of critical discourse analysis. The corpus analysis tool AntConc 3.5.9 is used to conduct concordance analysis, and KH Coder 3 is used to draw the co-occurrence network of words. It is found that, in the context of carbon peak and carbon neutrality, the image of China is characteristic of strong determination to achieve the “dual carbon” goals, high sense of environmental governance responsibility, and active pursuit of technology innovations and international cooperation. The findings of this study can provide insights into the construction of the “dual carbon” discourse with Chinese characteristics and the global dissemination of the positive national image of China in building a community with a shared future for mankind.